2006
DOI: 10.1111/j.1083-6101.2005.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

“He Will Crush You Like an Academic Ninja!”: Exploring Teacher Ratings on Ratemyprofessors.com

Abstract: This study examines students' motives for use and perceptions of the web site http://www.ratemyprofessors.com, one of the main sites that allow students to post anonymous ratings of college professors in the United States and Canada. The contents of comments posted to the web site are examined for relationships to numerical ratings on the site and motivations expressed by students for participating in the rating process. Qualitative (focus group interviews) and quantitative (content analysis) investigations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 23 publications
5
70
0
Order By: Relevance
“…Various coding schemes have been developed for a variety of topics, ranging from user comments on machine learning [19], over student comments on the teaching performance of professors [20] to YouTube comments [21]. [22] applied PD in a school setting to plan and improve lessons together with students and developed a coding scheme to code the spoken comments made during discussions.…”
Section: Related Workmentioning
confidence: 99%
“…Various coding schemes have been developed for a variety of topics, ranging from user comments on machine learning [19], over student comments on the teaching performance of professors [20] to YouTube comments [21]. [22] applied PD in a school setting to plan and improve lessons together with students and developed a coding scheme to code the spoken comments made during discussions.…”
Section: Related Workmentioning
confidence: 99%
“…"A primary reason for the popularity of online teacher rating sites is, arguably, students" desire for information about classes and professors. Unlike traditional course evaluations where the audience is the teacher and perhaps administrators, the intended audience for RMP and other similar sites is other students (Kindred and Mohammed, 2005). "…”
Section: Results From Previous Studymentioning
confidence: 99%
“…In focus group studies by Kindred and Mohammed (2005) students showed they were wary of trusting the evaluations at RMP, but continued to use them as a supplement. Clearly, they want as much information about courses and teachers as they can get, even if the source is somewhat questionable.…”
Section: Results From Previous Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To examine students' comments and ratings of 626 professors teaching different disciplines at a U.S. university at RateMyProfessor.com using a survey and a focus group interview, Kindred and Mohammed (2005) found that students' comments focused on the professor's competence including clarity of instruction and personality traits such as focused, energetic, inspiring, helpful and easy. Overall, students' concern was for teacher competence more than appearance or personality.…”
Section: Students' Perceptionmentioning
confidence: 99%